The Corticotropin Releasing Hormone-1 (CRH1) Receptor Antagonist Pexacerfont in Alcohol Dependence: A Randomized Controlled Experimental Medicine Study - Kwako, Laura E (Neuropsychopharmacology, 2015)
Extensive preclinical data implicate corticotropin-releasing hormone (CRH), acting through its CRH1 receptor, in stress- and dependence-induced alcohol seeking. We evaluated pexacerfont, an orally available, brain penetrant CRH1 antagonist for its ability to suppress stress-induced alcohol craving and brain responses in treatment seeking alcohol-dependent patients in early abstinence. Fifty-four anxious alcohol-dependent participants were admitted to an inpatient unit at the NIH Clinical Center, completed withdrawal treatment, and were enrolled in a double-blind, randomized, placebo-controlled study with pexacerfont (300 mg/day for 7 days, followed by 100 mg/day for 23 days). After reaching steady state, participants were assessed for alcohol craving in response to stressful or alcohol-related cues, neuroendocrine responses to these stimuli, and functional magnetic resonance imaging (fMRI) responses to alcohol-related stimuli or stimuli with positive or negative emotional valence. A separate group of 10 patients received open-label pexacerfont following the same dosing regimen and had cerebrospinal fluid sampled to estimate central nervous system exposure. Pexacerfont treatment had no effect on alcohol craving, emotional responses, or anxiety. There was no effect of pexacerfont on neural responses to alcohol-related or affective stimuli. These results were obtained despite drug levels in cerebrospinal fluid (CSF) that predict close to 90% central CRH1 receptor occupancy. CRH1 antagonists have been grouped based on their receptor dissociation kinetics, with pexacerfont falling in a category characterized by fast dissociation. Our results may indicate that antagonists with slow offset are required for therapeutic efficacy. Alternatively, the extensive preclinical data on CRH1 antagonism as a mechanism to suppress alcohol seeking may not translate to humans.